Изучение возможностей прогнозирования эффективности мутагенных воздействий на примере озимой мягкой пшеницы - Эйгес, Н.С.; Волченко, Г.А.; Волченко, С.Г. (Фактори експериментальної еволюції організмів, 2016)
Aim. To establish the possibility of prognosis the effectiveness of mutagenic influences on winter wheat. Methods. Chemical mutagenesis. Use of chemical mutagen ethyleneimine on highmutability variety PPG 186. Results. The possibility of prognosis the effectiveness of mutagenic influences on the basis of various indicators. Conclusions. The indicators found of mutagenic influences: the choice of the initial variety; the nature of the curve of M1 with extrapolation on the M2 and on the next generations; specificity of mutagenic influences; the presence of similar non-scissile (stable) in M2 families without chimeras in M1; in presence of marker signs. Keywords: chemical mutagenesis method, supermutagen ethyleneimine, generations, winter wheat, the efficiency of mutagenesis treatment, prognosis.